Impending Crisis in Rural Sri Lanka - Wimalaratana, Wijitapura (University of Colombo, 2010)
Sri Lanka had a rural sector dominated economy before the socioeconomic transformation under the British rule. It mainly rotated around the subsistence economy consisting of rice cultivation, home gardening and shifting agriculture (Chena cultivation) and the village was the social grouping in this setup. The prominent place that the rural sector had retained for centuries began to decline along with the booming plantation culture although the overwhelming majority of the natives used to live in this sector even well into the political independence. The centuries old economic system that the country had inherited was renamed as domestic or traditional sector to distinguish it from the newly introduced colonial plantation culture in the economic literature. Rural sector has been considered as the development trump card of the country during the most part of post independent period, especially up to the economic liberalization of 1977. Services and export promotion industrialization elements were markedly introduced to the development equation of the post liberalization period although traditional rhetoric on domestic agriculture and the rural sector did not disappeared at all instantly. The rural economy has traditionally been rotated around the domestic agriculture. Availability of sufficient lands for agriculture and related activities and utilization of such resources on sustainable manner are pre requisites to maintain the centuries old socioeconomic and environmental equilibrium in the sector. On going economic practices in rural Sri Lanka is checking the long-term sustainability of the sector. Now a crisis situation is looming in the near horizon of the rural sector and it is originating from different corners of the economy and society. Horizontal expansion of unplanned housing settlements and related facilities such as roads, water, electricity and other common amenities are swallowing up lands meant for rural agriculture and related activities. Similarly, authorized and unauthorized filling up of paddy fields, clearance of forest lands, garbage disposable problems, water logging and other environmental problems have become part and parcel of this practice. This trend is directly attacking to the very foundation of the rural sector and it is quite visible in the fast growing western province and adjoining provinces although other provinces are not totally immune to this practice. In certain localities where the gravity of the practice is so high, lands are available only for settlements and not for the domestic agriculture and related activities. There is a clear tend of the disappearing of the centuries old rural economy in fast growing areas of the country. Unchecked land fragmentation is also going on all over the country adding more lands into uneconomical farm-size category. It is emanating mainly from two sources as commercial land sales for housing purpose and the division of ancestral lands among family members. The situation is aggravated slowly but surely; as a result of the population growth in the country and lack of national policy on land partition. The apparent outcome will be the accumulation of fallow lands, especially in the rice sector. The trend is further strengthened by the opening up of new income avenues in the industrial and service sectors in more developed areas of the country. Poverty is the obvious result in areas 55 where such alternative income sources are not available and village community engage in economic activities in economically unsustainable small plots of lands. The contours of traditional rural sector are also disappearing now. All village lands including the catchment areas of irrigation tanks, reservation lands, village forests and common areas are been encroached and used for housing settlements and other purposes. The village identity and centuries old socioeconomic and environmental equilibrium is gradually disappearing. As a result of the ongoing transformation process, the rural areas of the economy are turning into semi urban areas yet without basic urban facilities. This unplanned and uninterrupted process is going on making devastative socioeconomic and environmental issues in rural Sri Lanka. In the near future this will reach to a crisis and unmanageable point once the transformation process envelops many rural areas of the country. Information for the proposed article is mainly collected from secondary sources. In addition that, complementary information is collected from the field observation, interviewing of informed individuals, public officials and the focus groups in the society and public officials.